KODE ETIK JURNALISTIK DALAM TAYANGAN BERITA KANJURUHAN DI NARASI NEWSROOM - Hemalindha, Hemalindha Syarifah Hanum; Suryo, Herning; Maserona Sarungu, Lukas (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
This research aims to find and describe violations of the Journalistic Code of Ethics in Narasi Newsroom media in news videos of Brutal Moments Leading Up to Mass Death. In this research, researchers used the Social Responsibility Press Theory which is used in the Indonesian press. The research method used is a qualitative descriptive method with a content analysis approach. Researchers used source triangulation techniques to ensure the data used was correct and valid and used the interactive method Miles, Huberman and Saldana in the process of analyzing the data. Based on research analysis, the Newsroom narrative in the news video entitled Brutal Moments Leading Up to Mass Death in the Kanjuruhan Incident has committed several violations of the Journalistic Code of Ethics. Some of these violations refer to sensational news. Sensational news itself is a strong violation of the Journalistic Code of Ethics and Social Responsibility Press Theory. However, sensational news is often used to increase the number of clickers and viewers in order to fulfill competition and profit motives. Judging from these problems, it can be said that the Press Theory of Social Responsibility cannot be implemented optimally because the freedom of the press is not in line with the responsibilities imposed on the press media.